The Impact of New Actors on the Global Economy – an Attempt to Asses Using the Example of the BRICS Countries - Czech, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The evolution of the global economy has led to the emergence of new, important entities on the international arena, among which, undoubtedly, are the BRICS countries. The growth of their importance is reflected, inter alia, in the increase of their share of global revenue and the value of their currency reserves. For several years, the BRICS countries have sought a more formal recognition of their growing importance in the global economy, which has led to the establishment of their joint development bank and their own reserve funds. This study assesses the significance of the BRICS group as a subject of the global economy in the early years of the 21st century, in comparison to traditional economic powers. It contains descriptive and comparative analysis, as well as a systematisation of statistical information and observations. The analysis shows that the BRICS countries will continue contributing to the changes occurring in the global economy in the coming years. The study also looks at problems that may hinder the rapid development of these countries, including, environmental issues, international conflict, disease and terrorism.